2020
DOI: 10.1002/jccs.202000130
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, in vitro cytotoxicity, ADME, and molecular docking studies of benzimidazole‐bearing furanone derivatives

Abstract: A series of benzimidazole‐derived–furanones (4a–l) were synthesized, characterized, and explored for their in vitro anticancer activities. The pharmacokinetic parameters assessed revealed that all the compounds followed the Lipinski's rule of five, making them potential drug candidates. Further, the results of anticancer activity revealed that (E)‐5‐(1H‐benzo[d]imidazol‐2‐yl)‐3‐(3,4,5‐trimethoxybenzylidene)furan‐2(3H)‐one (4a), was active against A549, MCF7, and DU145 with an IC50 values of 10.4 ± 0.39, 11.1 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 51 publications
(42 reference statements)
1
13
0
Order By: Relevance
“…Husain et al prepared various derivatives of furanone appended benzimidazoles, which effectively contribute to cancer therapy [53]. Compound (40) was found active against DU145 and MCF7 whereas compound (41) has got excellent activity against MCF7, A549, and DU145 cell lines (Figure 11).…”
Section: Anticancer Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Husain et al prepared various derivatives of furanone appended benzimidazoles, which effectively contribute to cancer therapy [53]. Compound (40) was found active against DU145 and MCF7 whereas compound (41) has got excellent activity against MCF7, A549, and DU145 cell lines (Figure 11).…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Benzene-1,2-diamine undergoes condensation reactions with anthranilic acid, 3, 5-dinitrophenylbenzoic acid, and phenylacetic acid, catalyzed by NH 4 Cl yielded the precursor molecules, which on reaction with electrophile-releasing agents produced the corresponding o-substituted and 1,2-disubstituted benzimidazoles (52) and (53), respectively (Figure 13). In vitro studies of these compounds showed a better activity with a low minimum inhibitory concentration (MIC) value.…”
Section: Antibacterial and Antifungal Activitymentioning
confidence: 99%
“…1 H-NMR (300 MHz, DMSO-d 6 ): δ = 1.35 (3H, t, J=6.90 Hz, -CH3), 3.07-3.20 (4H, m, piperazin), 3.63-3.70 (4H, m, piperazin), 4.10 (2H, q, J=6.93 Hz, -CH2), 4.61 (2H, s, -CH 2 ), 6.97-7.01 (4H, m, Aromatic C-H), 7.02-7.10 (2H, m, Aromatic C-H), 7.52-7.56 (1H, m, benzimidazole-C4), 7.58 (1H, dd, J 1 =8.37 Hz, J 2 =1.56 Hz, benzimidazole-C5), 8.02 (1H, s, benzimidazole-C7), 8.17(2H, d, J= 8.82 Hz, 1,4-disubstituted benzene). 13…”
Section: Chemistrymentioning
confidence: 99%
“…It is observed that hydrogen bond donor and acceptor sites, that is, N1 and N3 in the benzimidazole core, play a critical role in binding to the biological targets [12]. In recent studies, potential anticancer activity has been noted in compounds to which benzimidazole is linked by other heterocyclic rings [13][14][15][16]. The benzimidazole ring has been applied to various marketed anticancer drugs such as bendamustine, veliparip, carbendazim, and nocodazole (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular docking can help to predict the most energetically favorable binding pose of a ligand to its receptor in terms of the binding energy. [31][32][33] EGFR (epidermal growth factor receptor) is a transmembrane glycoprotein having a mass of ∼ 180 kDa containing-i) an extracellular domain, ii) single transmembrane domain, and iii) intracellular tyrosine kinase domain. [34][35][36] Within the extracellular domain lies a ligandbinding cleft that can interact with a number of various ligands, including EGF and TGF-α.…”
Section: Molecular Dockingmentioning
confidence: 99%